2017
DOI: 10.1590/1809-4430-eng.agric.v37n1p1-12/2017
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics (Cfd) Application for Ventilation Studies in Broiler Houses

Abstract: ABSTRACT:With the recent increase in the number of acclimatized broiler houses in Brazil, design and adaptation of facilities to withstand the tropical weather conditions enabling the maintenance of ideal conditions without increasing costs have been major challenges. The aim of this study was to evaluate the ventilation system in solid-wall broiler houses using computational fluid dynamics (CFD). The research was carried out in the city of Amparo -SP (Brazil). The facility consisted of a broiler house enclose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…Xue et al (2016) calculated the average NMSE of 0.15 and considered its CFD model to be valid for analyzing the effects of cooling pad installation on airflow distribution in tunnelventilated laying-hen houses. Curi et al (2017b) found NMSE equal to 0.19 for air velocity and validated a CFD model, generated in Ansys CFX 14.0 software, of a broiler house ventilated with negative pressure. Saraz et al (2011) found a maximum NMSE of 0.0035 for air temperature and validated a simulation model to estimate air temperature distribution in poultry house with tunnel ventilation system.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Xue et al (2016) calculated the average NMSE of 0.15 and considered its CFD model to be valid for analyzing the effects of cooling pad installation on airflow distribution in tunnelventilated laying-hen houses. Curi et al (2017b) found NMSE equal to 0.19 for air velocity and validated a CFD model, generated in Ansys CFX 14.0 software, of a broiler house ventilated with negative pressure. Saraz et al (2011) found a maximum NMSE of 0.0035 for air temperature and validated a simulation model to estimate air temperature distribution in poultry house with tunnel ventilation system.…”
Section: Resultsmentioning
confidence: 57%
“…The validation of the reference model for the variables T air , RH and V air was performed by comparing the simulation results and their correspondents obtained experimentally. A procedure adopted by Saraz et al (2011); Xue et al (2016) and Curi et al (2017b) was used, in which the normalized mean squared error (NMSE) is calculated according to Eq. 3, and NMSE values less than 0.25 are acceptable as good indicators of agreement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For alternative boundary conditions, convective heat transfer coefficient (h, W m -2 K -1 ) results in higher values for NMSE in both variables; temperature is ~4%, and airflow speed is ~22% (Camargo, 2015; for details in simulation and results). NMSE values below 25% are indicative of a good correlation between simulation and experimental results (Curi et al, 2017). Homogeneous environmental conditions can be obtained with the control of ventilation systems (Calvet et al, 2011;Bustamante et al, 2013), while literature reference values for air speed are 1.5-2.5 m s -1 (Bustamante et al, 2015).…”
Section: Resultsmentioning
confidence: 92%
“…For mesh details, see Camargo (2015). A CFD validation analysis was performed by NMSE -Normalized Mean Square Error methodology (Curi et al, 2017).…”
Section: Numerical Model Cfd Simulation and Validationmentioning
confidence: 99%